Low Global Warming C4H3F7O Isomers for Plasma Etching of SiO2and Si3N4Films - Kim, Yongjae; Kim, Seoeun; Kang, Hojin; You, Sanghyun; Kim, Changkoo; Chae, Heeyeop (ACS Sustainable Chemistry and Engineering, 2022)
In this study, the plasmas of C4H3F7O fluoro-ether and fluoro-alcohol isomers of CF3CF2CF2OCH3(HFE-347mcc3), (CF3)2CFOCH3(HFE-347mmy), and CF3CF2CF2CH2OH (PPC) with low global warming potentials (GWPs) were characterized for etching SiO2, Si3N4, and poly-Si films. The C4H3F7O isomers have a short lifetime (<5 years) and low GWP (<1000) compared to the widely used C4F8, with a lifetime of 3200 years and a GWP100of 10,592. Radicals in the plasma of C4H3F7O fluoro-ethers and fluoro-alcohol isomers were analyzed by mass spectroscopy, and HF and CO peaks were identified as major gas-phase products in the plasma phase. The concentration of exhaust gases after plasma etching were analyzed, and the million metric tons of carbon equivalent (MMTCE) were determined relative to conventional perfluorocarbon (PFC), C4F8. HF, CO, and COF2were identified as the major reaction products in exhaust with C4H3F7O isomer plasmas. The MMTCEs of HFE-347mcc3, HFE-347mmy, and PPC were lowered by 82, 74, and 85%, respectively, compared with that of C4F8. The chemical bonding of the steady-state fluorocarbon film on SiO2, Si3N4, and poly-Si surfaces was analyzed during the etching process, and a lower F 1s/C 1s ratio was observed for C4H3F7O isomers than for C4F8. A high etch selectivity of 170 was achieved for SiO2etching over poly-Si and 263 for Si3N4etching over poly-Si with PPC plasma. This high selectivity is attributed to the higher carbon and lower fluorine contents in the steady-state fluorocarbon film. The C4H3F7O isomer plasmas also generate a superior etch profile compared to the C4F8plasma with an aspect ratio of 7:1 etch of 200 nm hole patterns. This study demonstrates that C4H3F7O isomers can significantly reduce the global warming effect by replacing the conventional PFC in the etching processes of semiconductor device fabrication.
Keywords: Carbon equivalent; Etch selectivity; Etching process; Fluorocarbon films; Global warming potential; Low global warming potential; Million metric ton of carbon equivalent; Perfluorocarbons; Poly-Si films; Steady state; etch selectivity; low GWP; MMTCE; PFC; plasma etching